Main determinants of Croatian national security policy during the 1995-2013 period - Paszkiewicz, Jędrzej (Balcanica Posnaniensia. Acta et studia, 2013)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article investigates the factors which determined the evolution of the national security concept in the Republic of Croatia during the period 1995-2013, as viewed by the political elite as well as the Croatian society. The Croatian public discourse approaches the national security in the context of either a multi-faceted reform of the country’s security sector or an improvement of both the democratic control over the military and security forces. Among the former Yugoslav republics, Croatia accomplished major goals in its pursuit of the national security policy. After a period of arduous reforms and reconstruction, the country has become a member of both the NATO and the European Union. The issues which are still disputed among the researchers are the legal bases for the security policy and the process of the internalization of values lying at the foundation of the security sector reform. It is questionable whether or not the newly established system of legal and institutional references is likely to consolidate in the social, political and economic reality of modern Croatia.